Endoplasmic Reticulum Protein Quality Control and Its Relationship to Environmental Stress Responses in Plants - Liu, Jian-Xiang; Howell, Stephen H. (The Plant cell, 2010)
The endoplasmic reticulum (ER) has a sophisticated quality control (QC) system to eliminate improperly folded proteins from the secretory pathway. Given that protein folding is such a fastidious process and subject to adverse environmental conditions, the ER QC system appears to have been usurped to serve as an environmental sensor and responder in plants. Under stressful conditions, the ER protein folding machinery reaches a limit as the demands for protein folding exceed the capacity of the system. Under these conditions, misfolded or unfolded proteins accumulate in the ER, triggering an unfolded protein response (UPR). UPR mitigates ER stress by upregulating the expression of genes encoding components of the protein folding machinery or the ER-associated degradation system. In Arabidopsis thaliana, ER stress is sensed and stress signals are transduced by membrane-bound transcription factors, which are activated and mobilized under environmental stress conditions. Under acute or chronic stress conditions, UPR can also lead to apoptosis or programmed cell death. Despite recent progress in our understanding of plant protein QC, discovering how different environmental conditions are perceived is one of the major challenges in understanding this system. Since the ER QC system is one among many stress response systems in plants, another major challenge is determining the extent to which the ER QC system contributes to various stress responses in plants.